PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AKSESORIS HANDPHONE PADA HEZAL CELLULAR DI KOTA TANGERANG - Nadia; Andalusi, Ratih (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of promotion and product quality on purchasing decisions for cellphone accessories at Hezal Cellular in Tangerang City. The method used is quantitative. The technique used is quantitative. The sampling technique used the slovin formula and obtained a sample of 125 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results showed, t count 18.198> t table 1.976, and or a significance value of 0.000 <0.05 then H0 was rejected and Ha was accepted. While the results of the coefficient of determination R Square = 0.821 or 82.1%, it can be concluded that the contribution of Promotion (X1) to Purchasing Decisions (Y) is 82.1% and the remaining 17.9% is influenced by other factors. There is a partial effect of product quality on the purchase of cellphone accessories at Hezal Cellular in Tangerang City, t count 18.198> t table 1.976, and or a significance value of 0.000 <0.05 then H0 is rejected and Ha is accepted. While the results of the coefficient of determination R Square = 0.729 or 72.9%, it can be concluded that the contribution of Product Quality (X2) to Purchasing Decisions (Y) is 72.9% and the remaining 27.1% is influenced by other factors. There is a simultaneous influence of Promotion and Product Quality on Purchasing Decisions for Cellphone Accessories at Hezal Cellular in Tangerang City. With a calculated F value of 316.339> F table 3.070, and or a significance value of 0.000 <0.05, H0 is rejected and Ha is accepted. While the results of the coefficient of determination R Square = 0.838 or 83.8%, it can be concluded that the contribution of Promotion (X1) and Product Quality (X1) to Purchasing Decisions (Y) is 83.8% and the remaining 16.2% is influenced by other factors.